Dimensi-Dimensi dalam Beragama: Spiritual, Intelektual, Emosi, Etika, dan Sosial - Ambo Dalle; Tobroni Tobroni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the dimensions of religiosity, encompassing spiritual, intellectual, emotional, ethical, and social aspects. Using library research methods, the research delves into the interactions and contributions of each dimension to religious experiences through a comprehensive analysis of various academic literature.The research findings reveal that religious dimensions are interconnected and influence individual spiritual quality. The spiritual dimension relates to personal experiences and relationships with God, the intellectual dimension focuses on understanding religious teachings, the emotional dimension regulates responses to religious practices, the ethical dimension covers moral values, and the social dimension concerns interactions within religious communities.The study identifies key challenges in religiosity, such as religious shallowness and moral crisis. As a solution, the research offers a multidimensional Islamic Religious Education (PAI) design that integrates divine, humanistic, and natural values. This approach aims to form a generation with a balance between rationality, morality, and spirituality.The research conclusion emphasizes the importance of holistic religious guidance that encourages faith strengthening, critical education, and awareness of human responsibilities. This study provides a theoretical contribution to understanding the complexity of religious experiences and developing a responsive religious education model that addresses modern challenges.Keywords: Religious Dimensions, Islamic Religious Education, Spirituality, Multidimensional, Moral